Do English Skills Affect Muslim Immigrants' Economic and Social Integration Differentially? - Mutlu Yuksel; Mevlude Akbulut-Yuksel; Cahit Guven (Institute of Labor Economics (IZA), 2019)
This paper estimates the returns to English-speaking fluency on the socioeconomic outcomes of childhood immigrants. We further investigate whether Muslim childhood immigrants face additional hurdles in economic and social integration into the host country. Motivated by the critical age hypothesis, we identify the causal effects of English skills on socioeconomic outcomes by exploring the differences in the country of origin and age at arrival across childhood immigrants. We first document that all childhood immigrants who migrate from non-English-speaking countries at a younger age attain higher levels of English skills. We also find that acquiring better English-language skills improves the educational attainment and labor and marriage market prospects of non-Muslim childhood immigrants significantly and increases their participation in volunteer work. However, our results show that while a good command of English enhances the educational attainments of Muslim childhood immigrants, it shows no positive return in either the labor or marriage markets. Our results also show that progress in English fails to improve Muslim childhood immigrants' engagement in voluntary work, meaning that the opportunity for social cohesion is missed.
Keywords: J12; J13; J24; J31; J61; J62; 330; immigration; english proficiency; socioeconomic outcomes; Muslims